Systematic Assessment of Fragment Identification for Multitarget Drug Design. (4th February 2021) - Brunst, Steffen; Kramer, Jan S.; Kilu, Whitney; Heering, Jan; Pollinger, Julius; Hiesinger, Kerstin; George, Sven; Steinhilber, Dieter; Merk, Daniel; Proschak, Ewgenij
Abstract: Designed multitarget ligands are a popular approach to generating efficient and safe drugs, and fragment‐based strategies have been postulated as a versatile avenue to discover multitarget ligand leads. To systematically probe the potential of fragment‐based multiple ligand discovery, we have employed a large fragment library for comprehensive screening on five targets chosen from proteins for which multitarget ligands have been successfully developed previously (soluble epoxide hydrolase, leukotriene A4 hydrolase, 5‐lipoxygenase, retinoid X receptor, farnesoid X receptor). Differential scanning fluorimetry served as primary screening method before fragments hitting at least two targets were validated in orthogonal assays. Thereby, we obtained valuable fragment leads with dual‐target engagement for six out of ten target combinations. Our results demonstrate the applicability of fragment‐based approaches to identify starting points for polypharmacological compound development with certain limitations. Abstract : Thinking outside the pharmacophore : This study systematically investigates the potential of fragment‐based multiple ligand discovery. We employed a large fragment library for comprehensive screening on five targets and obtained valuable fragment leads with dual‐target engagement for six out of ten target combinations.